2017
DOI: 10.1186/s12974-017-0997-0
|View full text |Cite
|
Sign up to set email alerts
|

Blocking ATP-sensitive potassium channel alleviates morphine tolerance by inhibiting HSP70-TLR4-NLRP3-mediated neuroinflammation

Abstract: BackgroundLong-term use of morphine induces analgesic tolerance, which limits its clinical efficacy. Evidence indicated morphine-evoked neuroinflammation mediated by toll-like receptor 4 (TLR4) - NOD-like receptor protein 3 (NLRP3) inflammasome was important for morphine tolerance. In our study, we investigated whether other existing alternative pathways caused morphine-induced activation of TLR4 in microglia. We focused on heat shock protein 70 (HSP70), a damage-associated molecular pattern (DAMP), which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 75 publications
5
54
0
Order By: Relevance
“…Depending on the experiment, cell lines were treated with Wnt5a (100-200 ng/mL, R&D Systems, Bio-Techne, 645-WN-010), IFN-γ (100 ng/mL, BioAbChem, 42-IFNg), anti-PD-L1 Ab (1-2 μg/mL), HSP70 (1-10 μM, Enzo, ADI-ESP-502-D), HSP70 inhibitor (Thermo Fisher Scientific, VER155008), CLI-095 TLR4 inhibitor (3-10 μM, Invivogen, tlrl-cli95), TLR2-IN-C29 TLR2 inhibitor (1-10 μM, Glixx, GLXC-06203), MPLA TLR4 agonist (10 μM, Enzo, ALX-581-205-C100), LPS (10 ng, Millipore-Sigma, L4391-1MG), recombinant IL-1β (100-200 ng, BioLegend, IFN-γ stimulation also serves to facilitate NLRP3 priming by an alternative mechanism in tumor cells is currently being investigated. Interestingly, HSP70/TLR4 signaling, as described above, may also provide a positive feed-forward priming pathway capable of perpetuating NLRP3 activation in tumors (46). These studies reveal that NLRP3 inhibition phenocopied downstream TLR4 and CXCR2 inhibition, suppressing the recruitment of PMN-MDSCs as an adaptive resistance mechanism initiated by local CD8 + T cell activity.…”
Section: Methodsmentioning
confidence: 72%
“…Depending on the experiment, cell lines were treated with Wnt5a (100-200 ng/mL, R&D Systems, Bio-Techne, 645-WN-010), IFN-γ (100 ng/mL, BioAbChem, 42-IFNg), anti-PD-L1 Ab (1-2 μg/mL), HSP70 (1-10 μM, Enzo, ADI-ESP-502-D), HSP70 inhibitor (Thermo Fisher Scientific, VER155008), CLI-095 TLR4 inhibitor (3-10 μM, Invivogen, tlrl-cli95), TLR2-IN-C29 TLR2 inhibitor (1-10 μM, Glixx, GLXC-06203), MPLA TLR4 agonist (10 μM, Enzo, ALX-581-205-C100), LPS (10 ng, Millipore-Sigma, L4391-1MG), recombinant IL-1β (100-200 ng, BioLegend, IFN-γ stimulation also serves to facilitate NLRP3 priming by an alternative mechanism in tumor cells is currently being investigated. Interestingly, HSP70/TLR4 signaling, as described above, may also provide a positive feed-forward priming pathway capable of perpetuating NLRP3 activation in tumors (46). These studies reveal that NLRP3 inhibition phenocopied downstream TLR4 and CXCR2 inhibition, suppressing the recruitment of PMN-MDSCs as an adaptive resistance mechanism initiated by local CD8 + T cell activity.…”
Section: Methodsmentioning
confidence: 72%
“…An increasing number of studies have revealed that several brain regions, such as the ventral tegmental area (VTA), nucleus accumbens (NAc), and hippocampus (Hipp), are involved in morphine addiction (Kim et al, 2016). Although mechanisms underlying morphine-mediated processes remain the subject of much debate, morphine stimulation activates G protein-coupled opioid receptors and then induces significant molecular changes inside the cell, such as an inhibition of adenylate cyclase activity, and activation of potassium channels (Qu et al, 2017;Yang et al, 2019). In addition, other signalling pathways, including mitogenactivated kinases (MAPK), b-arrestin, phospholipase C, protein kinase, PI3K, and extracellular signal-regulated kinase (ERK) pathways, are also involved in morphine activity (Bianchi et al, 2010;Zhang and Pan, 2010;Dai et al, 2018;Shen et al, 2018;de Freitas et al, 2019;Dekan et al, 2019;Listos et al, 2019).…”
Section: Morphine Addictionmentioning
confidence: 99%
“…30,31 Neuroinflammation has been heavily implicated in the formation of morphine-induced antinociceptive tolerance. 32 Inhibiting NLRP3 signaling to decrease neuroinflammation has been reported to alleviate morphineinduced antinociception tolerance in previous studies 3,5,33,34 Furthermore, with regard to neuropathic status, miR-223 has been reported to downregulate and suppress the activities of the NLRP3 inflammasome to relieve morphine-induced antinociception tolerance in rats. 35 Studies have shown that morphine can also modulate immune responses by promoting IL-1β release, while the inhibition of IL-1β prevents morphine-induced antinociception tolerance.…”
Section: Discussionmentioning
confidence: 97%